Tinjauan Yuridis Sengketa Informasi Publik dalam Administrasi Negara: Studi Kasus Putusan PTUN Nomor 410/G/KI/2024/PTUN.JKT - Esra Natasya Sitepu; Ivana Theo Philia; Jekson Saragih; Nazlah Aulia; Rani Oktavia Purba; Ture Ayu Situmeang; Taufiq Ramadhan; Jahya Adiputra Simbolon (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to analyze the legal aspects of public information disputes in the context of state administration, focusing on the Decision of the Jakarta State Administrative Court (PTUN) Number 410/G/KI/2024/PTUN.JKT. A public information dispute is a dispute between a public agency and an information applicant regarding the right to obtain and use public information based on laws and regulations. In the era of globalization and the development of information technology, access to public information is one of the important pillars in realizing transparent and accountable governance. In Indonesia, the right to public information is guaranteed by Law Number 14 of 2008 concerning Openness of Public Information (UU KIP). However, in practice, disputes often occur between public agencies and the public regarding the fulfillment of the right to information. The Decision of the Jakarta PTUN Number 410/G/KI/2024/PTUN.JKT is an important case study because it reflects the dynamics of law in resolving public information disputes at the state administration level. This study uses a normative legal approach with a case study method. Data were obtained from the analysis of PTUN Jakarta decisions and related legal documents. The results of the study show that public information disputes often occur due to unclear boundaries between information that can be accessed by the public and that which must be protected. The Jakarta PTUN decision emphasizes the importance of consistency in the application of the Consequence Test Sheet and emphasizes that information related to public services must be open to public access. This study contributes to understanding the legal complexity behind public information disputes and provides recommendations for improving the dispute resolution system in the future. In addition, this study also reminds us of the importance of a balance between public information transparency and personal data protection, especially in the context of state administration.